Motricidad fina y su incidencia en el aprendizaje para mejorar el rendimiento académico de los estudiantes del cuarto año de educación básica de la Unidad Educativa Caracol del cantón Babahoyo, Provincia de Los Ríos - Moreira Contreras, Monica Alexandra (2019)
The present research project refers to information. The information on the subject. The snail of the canton. Babahoyo of the province of Los Ríos.; The analysis of the subject in this population, the benefit of the boys and the girls, the digital work and the press, the set of the harmony and the precision of the movements. and innovative play methods, results in the development of skills, potentialization of maturational processes: socio-affective, motor and cognitive of each student, providing an integral development. The methodology applied is the qualitative and quantitative design, since we have verified the questions. the data collection instruments allowed us to observe and show the reality that in the subsequent one the respective conclusions and recommendations were raised.